Innovative Strategies in Managing Human Resources in the Digitalization Era of Education: A Progressive Academic Perspective - Hegar Harini; Ahmad Jauhari Hamid Ripki; Sulistianingsih; Herlina; Syamzah Ayuningrum (Politeknik Ganesha Medan, 2024)
The development of information and communication technology has brought fundamental changes in educational approaches. Digitalization has altered how we access, manage, and deliver information in academic settings. This research aims to examine innovative strategies in managing human resources in the digitalization era of education. The research method employed is a qualitative literature review utilizing data from Google Scholar spanning from 2017 to 2023. The research process begins with the identification of relevant keywords. The study findings indicate that in the continually evolving era of educational digitalization, innovative strategies in managing human resources are crucial for educational institutions to remain relevant and competitive. Educational institutions need to adopt an adaptive and proactive approach in managing human resources. This involves recognizing the paradigm shifts in learning and teaching and ensuring that staff possess the necessary skills and expertise in information and communication technology.